The correlation between body mass index and postural control in individuals with obesity class I and normal BMI in 20-35 year-old - Chaiut, Wilawan; Lapprasitsuk, Parichat; Jantarawanich, Warisra; Boonsrimar, Sirikunlayar (Journal of Associated Medical Sciences, 2017)
Background: Obesity, as classified by body mass index (BMI), is a term used to describe a person who is very overweight, with a lot of body fat, which negatively affects to health especially balance and postural control in individuals with obesity. Objectives: To evaluate the correlation between BMI and postural control in normal individuals and individuals with obesity class I. Materials and methods: Thirty-two young healthy adults aged between 20 to 35 years old from Mae FahLuang University; Chiang Rai were recruited. Participants were divided by BMI into 2 groups; normal BMI group (BMI=18.5-22.99 kg/m2, N=16) and obesity class I group (BMI=25.0-29.99 kg/m2, N=16). The participants were assessed balance using Romberg test, Sharpened Romberg test, Dominant leg standing test, and Ipsilateral remembered matching task. Data were analyzed by Pearson correlation which p value was established at <0.05 to determine the correlation between these variables. Results: In obesity class I group, BMI had a positive correlation with Ipsilateral remembered matching task of left leg (r=0.624, p=0.010), and Ipsilateral remembered matching task of non-dominant leg (r=0.610, p=0.012) in moderate level. Conclusion: These results indicated that BMI is not correlated with postural control in obesity class I groups.